Implementasi Akad Murabahah dan Musyarakah Mutanaqisah dalam Pembiayaan Kepemilikan Rumah pada Bank Syariah Indonesia - Asri Diah Susanti; Fiska Petricia (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
As the country with the largest Muslim population, Indonesia has great potential in developing Sharia economic systems, particularly in the banking sector. One of the largest Islamic banks in Indonesia is Bank Syariah Indonesia (BSI), which offers various banking products as solutions to improve the welfare of society. With the increasing demand for house ownership financing, BSI offers the BSI Griya product for financing the purchase of houses, shops, offices, or apartments, which can use two contract mechanisms, namely murabahah and musyarakah mutanaqisah. The purpose of this research is to further examine the BSI Griya house financing product so that the public understands the differences and advantages of Sharia financing compared to conventional bank loans. The research method used is qualitative descriptive. The results of the study provide a clear overview of the BSI Griya housing financing scheme with the murabahah and musyarakah mutanaqisah contracts.